125k views
0 votes
How do you find the equation of each function? Function A is f(x)=3x^2 and Function C is f(x)=18x-16. How do you get those? And then how do you get the equation for Function B? Thanks!

How do you find the equation of each function? Function A is f(x)=3x^2 and Function-example-1

1 Answer

11 votes

Answer:


f(x) = 3^x --- Function A


f(x) = x^2 - 5 --- Function B


f(x) = 18x -6 --- Function C

Explanation:

Solving (a): Equation of Function A

An exponential equation is represented as:


y = ab^x

From the graph of function A,


x = 0\ when\ y = 1


x = 1\ when\ y = 3

For:
x = 0\ when\ y = 1


y = ab^x becomes


1 = ab^0


1 = a


a =1

For:
x = 1\ when\ y = 3


y = ab^x becomes


3 = a*b^1


3 = a*b

Substitute 1 for a


3 = 1*b


3 = b


b = 3


y = ab^x becomes


y = 1*3^x


y = 3^x

Replace y with f(x)


f(x) = 3^x

Solving (b): Equation of Function B

A quadratic equation is represented as:


y = ax^2 + bx + c

From the table of function B,


x = 3\ when\ y =4


x = 5\ when\ y =20


x = 6\ when\ y =31

For:
x = 3\ when\ y =4


y = ax^2 + bx + c becomes


4 = a*3^2 + b*3 + c


4 = a*9 + 3b + c


4 = 9a + 3b + c

For
x = 5\ when\ y =20


y = ax^2 + bx + c becomes


20 = a*5^2 + b*5 + c


20 = a*25 + b*5 + c


20 = 25a + 5b + c

For
x = 6\ when\ y =31


y = ax^2 + bx + c becomes


31 = a*6^2 + b*6 + c


31 = a*36 + b*6 + c


31 = 36a + 6b + c

So, we solve for a, b and c in:


4 = 9a + 3b + c


20 = 25a + 5b + c


31 = 36a + 6b + c

Make c the subject in
4 = 9a + 3b + c


c = 4 - 9a - 3b

Substitute
c = 4 - 9a - 3b in
20 = 25a + 5b + c and
31 = 36a + 6b + c


20 = 25a + 5b + c becomes


20 = 25a + 5b + 4-9a-3b

Collect Like Terms


-4+20 = 25a -9a+ 5b -3b


16 = 16a+ 2b

Divide through by 2


8 = 8a + b


c = 4 - 9a - 3b


31 = 36a + 6b + c becomes


31 = 36a + 6b + 4 - 9a - 3b

Collect Like Terms


-4+31 = 36a - 9a+ 6b - 3b


27 = 27a+ 3b

Divide through by 3


9 = 9a + b

Solve for a and b in:
8 = 8a + b and
9 = 9a + b

Subtract both equations:


8 - 9 = 8a - 9a + b - b


8 - 9 = 8a - 9a


-1 = -a

Divide both sides by -1


1 = a


a = 1

Substitute 1 for a in
9 = 9a + b


9 = 9*1 + b


9 = 9 +b

Subtract 9 from both sides


9-9=9-9+b


0=b


b = 0

Substitute
b = 0 and
a = 1 in
c = 4 - 9a - 3b


c = 4 - 9*1-3*0


c = 4 - 9-0


c = -5

So, the equation is:


y = ax^2 + bx + c


y=1*x^2 +0*x-5


y=x^2 -5

Replace y with f(x)


f(x) = x^2 - 5

Solving (c): Equation of Function C

This is calculated using:


f(x) =a + (x -1)d

Where


a = 12 -- the first term

d = the difference between successive terms


d = 30 -12 = 48-30 = 66 -48


d =18

So, we have:


f(x) =a + (x -1)d


f(x) = 12 + (x - 1)*18

Open bracket


f(x) = 12 + 18x - 18

Collect Like Terms


f(x) = 18x - 18+12


f(x) = 18x -6

User Massimo Milazzo
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.